2010
DOI: 10.1002/smll.201001333
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Mesoporous α‐Fe2O3 (Hematite) Thin‐Film Electrodes for Application in High Rate Rechargeable Lithium Batteries

Abstract: Herein is reported the synthesis of ordered mesoporous α-Fe(2)O(3) thin films produced through coassembly strategies using a poly(ethylene-co-butylene)-block-poly(ethylene oxide) diblock copolymer as the structure-directing agent and hydrated ferric nitrate as the molecular precursor. The sol-gel derived α-Fe(2)O(3) materials are highly crystalline after removal of the organic template and the nanoscale porosity can be retained up to annealing temperatures of 600 °C. While this paper focuses on the characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 48 publications
5
127
1
Order By: Relevance
“…[3,8,18] During this research, we found that the use of hydrated cadmium and ferric nitrate salts gives the best results in terms of pore structure and material homogeneity. Synthesis carried out using other precursor combinations such as chlorides and acetylacetonates failed or produced illdefined materials (not shown) likely due to both the different sol-gel behavior and interactions with the KLE diblock copolymer.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…[3,8,18] During this research, we found that the use of hydrated cadmium and ferric nitrate salts gives the best results in terms of pore structure and material homogeneity. Synthesis carried out using other precursor combinations such as chlorides and acetylacetonates failed or produced illdefined materials (not shown) likely due to both the different sol-gel behavior and interactions with the KLE diblock copolymer.…”
Section: Resultsmentioning
confidence: 81%
“…This result is in line with our previous work on α-Fe 2 O 3 . [3] Therein, we showed that high-quality mesoporous thin films can be synthesized through facile polymer templating of hydrated ferric nitrate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For conventional lithium ion batteries, typical volumetric energy and power densities are around 10-60 mW h cm À 2 mm À 1 and 1-100 mW cm À 2 mm À 1 . It is possible to achieve higher power density, up to 1,000 mW cm À 2 mm À 1 , by using porous battery electrodes that reduce ion diffusion through the active anode and cathode materials, as well as designs that reduce ion diffusion time in the electrolyte and decrease electrical resistance in the electrodes [5][6][7][8][9][10][11] . Most publications on high-power batteries focus on either anode or cathode half cells, and show improved power density at the expense of energy density.…”
mentioning
confidence: 99%